From pressure in the pipeline to accelerating ascension: a survey to understand professional experiences of and opportunities for Canadian women in the healthcare sector - L. Desveaux; J. Pirmohamed; N. Hussain-Shamsy; C. Steele Gray (BMC, 2023)
Abstract Background Much has been written about the state and persistent lack of progress regarding gender equity and the commonly referenced phenomenon of a 'leaking pipeline'. This framing focuses attention on the symptom of women leaving the workforce, rather than the well-documented contributing factors of hindered recognition, advancement, and financial opportunities. While attention shifts to identifying strategies and practices to address gender inequities, there is limited insight into the professional experiences of Canadian women, specifically in the female-dominated healthcare sector. Methods We conducted a survey of 420 women working across a range of roles within healthcare. Frequencies and descriptive statistics were calculated for each measure as appropriate. For each respondent, two composite Unconscious Bias (UCB) scores were created using a meaningful grouping approach. Results Our survey results highlight three key areas of focus to move from knowledge to action, including (1) identifying the resources, structural factors, and professional network elements that will enable a collective shift towards gender equity; (2) providing women with access to formal and informal opportunities to develop the strategic relational skills required for advancement; and (3) restructuring social environments to be more inclusive. Specifically, women identified that self-advocacy, confidence building, and negotiation skills were most important to support development and leadership advancement. Conclusions These insights provide systems and organizations with practical actions they can take to support women in the health workforce amid a time of considerable workforce pressure.